answersLogoWhite

0


Best Answer

-1

User Avatar

Bria Cummerata

Lvl 10
โˆ™ 2021-03-01 17:17:37
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.79
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1518 Reviews
More answers
User Avatar

Wiki User

โˆ™ 2009-02-17 03:17:46

y = x^2 - 3x

y' = 2x -3

This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: The derivative of y x2 - 3x at the point?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is the derivative for 3x 1?

If y = 3x +- 1, the derivative with respect to x is y' = 3.


Derivative of y sin 3x 5?

The derivative of y = sin(3x + 5) is 3cos(3x + 5) but only if x is measured in radians.


How do you factor 3x3-x2y plus 12x-4y?

3x3 - x2y + 12x - 4y = x2*(3x - y) + 4*(3x - y) = (x2 + 4)*(3x - y)


What does the derivative formula mean?

The derivative of a curve is basically the slope of the curve. If we say, for example, that if y = 2x, the derivative is 2, that means that at any point the line has this slope. If we say that for the function y = x2, the derivative is 2x, that means that at any point "x", the slope is twice the value of "x".


What is the derivative and second derivative of lnx to the third power?

If you mean: y =(lnx)3 then: dy/dx = [3(lnx)2]/x ddy/dx = [(6lnx / x) - 3(lnx)2] / x2 If you mean: y = ln(x3) Then: dy/dx = 3x2/x3 = 3/x = 3x-1 ddy/dx = -3x-2 = -3/x2


How do you solve y equals x2-3x-20 using systems?

y = x2 - 3x - 20 is a formula linking two variables, x and y. It does not - indeed, it cannot - have a solution. The equation x2 - 3x - 20 = 0 has solutions at x = -3.217 and x = 6.217 approx.


How do you solve this problem it just says solve x2 plus 3y equals 7 3x plus y2 equals 3?

x2 + 3y = 7 3x + y2 = 3 3y = x2 + 7 y2 = -3x + 3 y = x2/3 + 7/3 y = ± √(-3x + 3) If you draw the graphs of y = x2/3 + 7/3 and y = ± √(-3x + 3) in a graphing calculator, you will see that they don't intersect, so that the system of the given equations has not a solution.


What is the parabola y equals -x2-3x plus 2?

It is the parabola such that the coordinates of each point on it satisfies the given equation.


What is the rate of change in the function y equals tan3x?

In this case, you'll need to apply the chain rule, first taking the derivative of the tan function, and multiplying by the derivative of 3x: y = tan(3x) ∴ dy/dx = 3sec2(3x)


Evaluate the expression if x2 and y3 3x plus y?

the answers is d


Y equals x2 plus 3x plus 2?

is a quadratic equation for y, in terms of x.


What is the gradient of the tangent to the curve at x equals 2 if Y equals x2?

Gradient to the curve at any point is the derivative of y = x2 So the gradient is d/dx of x2 = 2x. When x = 2, 2x = 4 so the gradient of the tangent at x = 2 is 4.

People also asked